(untitled) (Research, Society and Development, 2022)
Honey is a food product produced by honeybees, from the nectar of flowers or from the excretions of plant-sucking insects, which the bees collect, transform, combine with specific substances of their own, store and leave to mature in the combs of the hive. Most of the honeys are offered without registration, control and inspection, which facilitates the tampering of the product. This study aimed to determine and evaluate physicochemical characteristics of honey from bees of the genus Apis melífera produced and marketed in the city of Frei Martinho-PB. The two samples were collected directly from the Boa Sorte apiary in two different periods, January and March 2022. Physicochemical analyzes were carried out on samples 1 and 2, in order to verify acidity, water activity, hydroxymethylfurfural (HMF), humidity, Brix and color. The analyzed samples had water activity, acidity, humidity, Brix within the standard recommended by the literature. The HMF content in the samples was below the maximum recommended value, indicating that there was no adulteration or overheating of the analyzed honeys. Regarding the color, both samples were collected in different periods, and, due to the predominant type of flowering at the time, they have different colors. From the results, it is concluded that the honey is able to be commercialized and consumed.